The Nef Reaction of Isocyanides - La Spisa, Fabio; Tron, Gian Cesare; El Kaïm, Laurent (Synthesis, 2014)
The interaction of isocyanides with acyl chlorides was first reported by Nef in 1892. The resulting α-keto imidoyl chlorides may be hydrolyzed to form α-keto amides. Relatively few data are available on this reaction and the chemistry of α-keto imidoyl chlorides has been largely underestimated until some recent uses in intra- and intermolecular couplings with a variety of nucleophiles. The present review brings a comprehensive presentation of the Nef reaction of isocyanides focusing on mechanism and regioselectivity issues. 1 Isocyanide Chemistry2 Isocyanide Interaction with Acyl Chlorides and Analogues2.1 General Considerations2.2 Methods of Preparation of α-Keto Imidoyl Chlorides2.3 Nef Reaction Mechanism3 Reactivity of α-Keto Imidoyl Chlorides3.1 General Behavior of α-Keto Imidoyl Chlorides3.2 Intramolecular Trappings3.3 Intermolecular Trappings and Three-Component Reactions4 Extensions of the Nef Reaction 5 Conclusion
Keywords: isocyanides; Nef reaction; acyl chlorides; imidoyl chlorides; ketenes